2013
DOI: 10.1080/03630242.2013.815681
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation in Iraqi Kurdistan: Description and Associated Factors

Abstract: The high prevalence of female genital mutilation has been a concern in Iraqi Kurdistan. This study was undertaken to estimate its prevalence and describe factors associated with its occurrence. A cross-sectional survey was undertaken from March to April 2011 of females aged up to 20 years using interviews and clinical examination. The survey included 1,508 participants with mean age of 13.5 years (SD 5.6). Overall female genital mutilation prevalence was 23%, and the mean age at which it had been performed was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 10 publications
6
65
0
Order By: Relevance
“…In our study, having no school education was strongly associated with FGM/C, which is in line with previous studies . Refaat et al showed that urban and educated women's daughters are less likely to undergo FGM/C .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, having no school education was strongly associated with FGM/C, which is in line with previous studies . Refaat et al showed that urban and educated women's daughters are less likely to undergo FGM/C .…”
Section: Discussionsupporting
confidence: 92%
“…Some women might experience severe physical and mental health problems, while others may appear not to experience any side effect. In contrast, a study conducted in the UK reported that, nearly three quarters of the circumcised girls, who participated in the study, had the procedure performed safely by a doctor within a medical setting [48].…”
Section: Discussionmentioning
confidence: 91%
“…Social and cultural traditions are important reasons for practicing FGC in many settings, which in some instances surpass dictate of religion as the most common reason [19,25]. This is particularly true for Iraqi Kurdistan Region as two other studies have shown that social and cultural traditions are the main reasons for practicing FGC (40.7% to 46.7%) [8,9]. These two studies have also reported a relatively high proportion of women that supported continuation of FGC practice particularly the mutilated participants (36.6% and 28%).…”
Section: Discussionmentioning
confidence: 99%
“…Religious leaders take varying positions with regard to FGC: some promote it, some consider it irrelevant to religion, and others contribute to its elimination [26,27]. Two other studies from Kurdistan Region reported dictate of religion as a very important reason for practicing FGC (50.3% and 38.8%) [8,9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation